2020
DOI: 10.3390/ijms21165833
|View full text |Cite
|
Sign up to set email alerts
|

In Vitro Cell Sensitivity to Palytoxin Correlates with High Gene Expression of the Na+/K+-ATPase β2 Subunit Isoform

Abstract: The marine polyether palytoxin (PLTX) is one of the most toxic natural compounds, and is involved in human poisonings after oral, inhalation, skin and/or ocular exposure. Epidemiological and molecular evidence suggest different inter-individual sensitivities to its toxic effects, possibly related to genetic-dependent differences in the expression of Na+/K+-ATPase, its molecular target. To identify Na+/K+-ATPase subunits, isoforms correlated with in vitro PLTX cytotoxic potency, sensitivity parameters (EC50: PL… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2
1

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 51 publications
0
2
0
Order By: Relevance
“…This finding highlights the variable inter-individual sensitivity to PLTX, already noted in mice as variable lethality after repeated oral administration [61], and suggested by epidemiological data in humans [48,[50][51][52][53]. The different inter-individual sensitivity to PLTX could be related, at least in part, to genetic factors, such as a variable inter-individual expression of Na + /K + -ATPase subunits' isoforms, as suggested by an in vitro toxicogenetic study on human monocytes [71].…”
Section: Discussionmentioning
confidence: 92%
“…This finding highlights the variable inter-individual sensitivity to PLTX, already noted in mice as variable lethality after repeated oral administration [61], and suggested by epidemiological data in humans [48,[50][51][52][53]. The different inter-individual sensitivity to PLTX could be related, at least in part, to genetic factors, such as a variable inter-individual expression of Na + /K + -ATPase subunits' isoforms, as suggested by an in vitro toxicogenetic study on human monocytes [71].…”
Section: Discussionmentioning
confidence: 92%
“…It has been demonstrated that PLTX downstream effects (i.e., sustained cytotoxicity) appear to be correlated with the expression of specific subunit isoforms in the pump. In particular, the expression of the β2-and to a lesser extent the α3-isoform positively correlates with increased cell sensitivity to PLTX cytotoxicity [35]. PLTX interaction with the α-β ATPase heterodimer causes a permanent conformational change of the transmembrane pump into a non-selective monovalent cation channel [36,37].…”
Section: Palytoxins Mechanism Of Actionmentioning
confidence: 99%